Women in the "Kerangkeng" of Tradition: the Study on the Status of Women in Minangkabau - Azwar, Welhendri (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2017)
The system of values, norms and some stereotypes attached to women are one of the factors that giving influences on the position and relationships of women with men in the existing social structure. Each person embraces the system of values or norm which is a consensus and constructed by the community itself than from generation to generation. The emergence of social construction on the status and role of women is the result of the perspective of a community towards their biological differences between men and women. The perspective which then results in oppression, exploitation, and subordination of women in social relations are contextually strongly related to socio-cultural conditions at that time. This section will discuss how women are positioned in the social life and the perspective of the culture of its subordination. Next, it is also described how the emergence of patriarchal ideology, a system that accommodates the interests of men to dominate and control women, as a consequence of the understanding of the nature of women which biologically different to men. The hegemony of patriarchal ideology brings the social awareness for women to accept the conditions of subordination as a natural thing, which is wrapped by the products of culture and tradition. It includes how patriarchal ideology is giving the effect on the system and the tradition of marriage.